2019
DOI: 10.1186/s12917-019-2170-8
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines and lipopolysaccharides up regulate MMP-3 and MMP-13 production in Asian elephant (Elephas maximus) chondrocytes: attenuation by anti-arthritic agents

Abstract: BackgroundOsteoarthritis (OA), the most common form of arthritic disease, results from destruction of joint cartilage and underlying bone. It affects animals, including Asian elephants (Elephas maximus) in captivity, leading to joint pain and lameness. However, publications regarding OA pathogenesis in this animal are still limited. Therefore, this study aimed to investigate the effect of proinflammatory cytokines, including interleukin-1 beta (IL-1β), IL-17A, tumor necrosis factor-alpha (TNF-α), and oncostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Expressions of MMPs and ADAMTSs are both elevated in OA cartilage and activities of both MMPs and ADAMTSs are positively associated with cartilage degradation (29,30). Matrix-degrading enzymes secreted by chondrocytes (e.g., MMPs and ADAMTSs) degrade the extracellular matrix (ECM) of cartilage; these degraded ECM fragments further induce synovial inflammation and inflammatory factor generation, eventually resulting in cartilage damage and OA progression (31). In the ECM of OA cartilage, MMP-13 is the main degrading enzyme for collagen, and ADAMTS-5 is the major degrading proteinase for aggrecan (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of MMPs and ADAMTSs are both elevated in OA cartilage and activities of both MMPs and ADAMTSs are positively associated with cartilage degradation (29,30). Matrix-degrading enzymes secreted by chondrocytes (e.g., MMPs and ADAMTSs) degrade the extracellular matrix (ECM) of cartilage; these degraded ECM fragments further induce synovial inflammation and inflammatory factor generation, eventually resulting in cartilage damage and OA progression (31). In the ECM of OA cartilage, MMP-13 is the main degrading enzyme for collagen, and ADAMTS-5 is the major degrading proteinase for aggrecan (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of PGE 2 in vivo was associated with vasodilation, pain, redness and swelling of joints, cartilage corrosion and fluid extravasation (Fattahi & Mirshafiey, 2012). In addition, the increase of IL-1β can stimulate synovial fibroblasts, chondrocytes and osteoclasts to produce tissue-damaging matrix metalloprotease (MMP), leading to bone loss (Sirikaew et al, 2019). Numerous published reports have shown that osthole, cimifugin, 5-O-methylvisammioside, albiflorin, paeoniflorin and icariin, the active components of WBC, can directly or indirectly regulate nuclear factor kappa-B or other signal pathways and reduce the contents of inflammatory cytokines IL-1β and PGE 2 (Liu et al, 2020;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mouse chondrocytes can be used to mimic experimental OA in vitro. IL-1β treatment of chondrocytes upregulates the expression of catabolic factors, including MMP3 and MMP13 [ 42 , 43 , 44 , 45 ]. These proteases act as collagenase and promote the degradation of type II collagen, after cartilage destruction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These proteases act as collagenase and promote the degradation of type II collagen, after cartilage destruction [ 30 ]. Clinical data have shown that MMP3 and MMP13 are highly expressed in the cartilage of patients with arthritis, resulting in OA progression [ 44 ]. In the present study, safflower seed extract suppressed the expression of MMP3, MMP13, and ADAMTS5 induced by IL-1β stimulation in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%